"Zylon" Aerogels. Issue 10 (31st July 2018) - Chen, Meiling; Wang, Daolin; Yue, Mingli; Lin, Xiankun; Yang, Ming; He, Qiang
Abstract: Ultralight materials with challenging combinations of properties such as high mechanical stiffness at low density, high thermal and environmental stabilities, are hard to achieve. Here, poly( p ‐phenylene benzobisoxazole) (PBO) nanofibers derived from "super" fibers (Zylon) are assembled into a robust 3D porous structure, forming aerogels with integrated performance surpassing previously existing polymeric aerogels. "Zylon" aerogel has a specific compressive modulus of 72 MPa g −1 cm 3 at a density as low as 32 mg cm −3, low thermal conductivity (0.045 W m −1 K −1 ) at 500 °C, and an intrinsic moisture resistance. PBO nanofibers also empower "Zylon" aerogels with high thermal stability up to 692 °C, a near‐zero thermal expansion coefficient, and a superior fire‐retardant capability. These attractive multiparameter properties make "Zylon" aerogels highly competitive lightweight construction structures. The use of polymeric assembly units with intrinsic demanding characteristics represents an essential pathway toward rationalizing the design of high‐performance aerogels. Abstract : "Zylon" aerogels consisting of poly( p ‐phenylene benzobisoxazole) nanofibers integrate outstanding mechanical and thermal properties with high moisture resistance in 3D porous structures, representing a new spectrum of ultralight materials with desirable high performances in challenging conditions.